Shortening of 3'UTRs correlates with poor prognosis in breast and lung cancer. - Antonio Lembo; Ferdinando Di Cunto; Paolo Provero (PLoS ONE)
A major part of the post-transcriptional regulation of gene expression is affected by trans-acting elements, such as microRNAs, binding the 3' untraslated region (UTR) of their target mRNAs. Proliferating cells partly escape this type of negative regulation by expressing shorter 3' UTRs, depleted of microRNA binding sites, compared to non-proliferating cells. Using large-scale gene expression datasets, we show that a similar phenomenon takes place in breast and lung cancer: tumors expressing shorter 3' UTRs tend to be more aggressive and to result in shorter patient survival. Moreover, we show that a gene expression signature based only on the expression ratio of alternative 3' UTRs is a strong predictor of survival in both tumors. Genes undergoing 3'UTR shortening in aggressive tumors of the two tissues significantly overlap, and several of them are known to be involved in tumor progression. However the pattern of 3' UTR shortening in aggressive tumors in vivo is clearly distinct from analogous patterns involved in proliferation and transformation.